2020
DOI: 10.1111/1755-0998.13191
|View full text |Cite
|
Sign up to set email alerts
|

Combining genotype, phenotype, and environmental data to delineate site‐adjusted provenance strategies for ecological restoration

Abstract: Despite the importance of climate‐adjusted provenancing to mitigate the effects of environmental change, climatic considerations alone are insufficient when restoring highly degraded sites. Here we propose a comprehensive landscape genomic approach to assist the restoration of moderately disturbed and highly degraded sites. To illustrate it we employ genomic data sets comprising thousands of single nucleotide polymorphisms from two plant species suitable for the restoration of iron‐rich Amazonian Savannas. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 90 publications
1
42
0
1
Order By: Relevance
“…The assumption is that if observed and predicted scores group together it is an indication that observed genotypes are locally adapted, while the opposite will indicate no local adaptation. In line with the conceptual premise by Lesica and Allendorf (1999), Carvalho et al (2020) found that observed and predicted genotypes for the highly degraded restoration site did not cluster together in either species, while the opposite was observed for the moderately disturbed site. In the praxis, this result suggests that local provenances are optimal to restore the moderately disturbed site, whereas mixed seed could be the best strategy to revegetate the highly degraded mining site, as local plants are probably no longer adapted to their climate and soil conditions.…”
Section: Introductionsupporting
confidence: 69%
See 3 more Smart Citations
“…The assumption is that if observed and predicted scores group together it is an indication that observed genotypes are locally adapted, while the opposite will indicate no local adaptation. In line with the conceptual premise by Lesica and Allendorf (1999), Carvalho et al (2020) found that observed and predicted genotypes for the highly degraded restoration site did not cluster together in either species, while the opposite was observed for the moderately disturbed site. In the praxis, this result suggests that local provenances are optimal to restore the moderately disturbed site, whereas mixed seed could be the best strategy to revegetate the highly degraded mining site, as local plants are probably no longer adapted to their climate and soil conditions.…”
Section: Introductionsupporting
confidence: 69%
“…In this context, in this issue of Molecular Ecology Resources, Carvalho et al (2020) advance the use of landscape genomic tools by developing a comprehensive approach to guide prerestoration provenance decisions across sites with varying environmental and disturbance regimes by considering both neutral and adaptive genetic variation via single nucleotide polymorphisms (SNPs) for two native plants (Dioclea apurensis and Mimosa acutistipula var. ferrea) of the Canga ecosystem in Brazil (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Jombart, Pontier and Dufour (2009) already mentioned that RDA was somewhat neglected in association studies despite now recognized desirable properties to limit false positives (Capblanc, Luu, Blum, & Bazin, 2018; Forester et al, 2018) and robustness to recombination rate variation (Lotterhos, 2019). Effectively, the use of RDA to investigate genotype-phenotype associations remains seldom (Talbot et al, 2017; Vangestel, Eckert, Wegrzyn, St. Clair, & Neale, 2018; Carvalho et al, 2020), while it became a standard in genotype-environment association studies (Forester, Lasky, Wagner, & Urban, 2018), including trout (Bekkevold et al, 2019). Basically, RDA allowed for distinguishing the part of variation collectively explained by RAD-loci and independent pigmentation variables, and hereby estimated to ∼35% of observed trait variation.…”
Section: Discussionmentioning
confidence: 99%